2020
DOI: 10.1007/s43032-020-00364-7
|View full text |Cite|
|
Sign up to set email alerts
|

The Involvement of Cell Adhesion Molecules, Tight Junctions, and Gap Junctions in Human Placentation

Abstract: Placentation is a major determinant of the success of pregnancy. It is regulated by several factors such as cell adhesion molecules, tight junctions, and gap junctions. The cell adhesion molecules are integrins, cadherins, immunoglobulins, nectins, and selectins. The tight junctions are composed of claudins, occludin, and junction adhesion molecule proteins while the gap junctions are composed of connexins of varying molecular weights. During placentation, some of these molecules regulate trophoblast prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 145 publications
2
23
0
6
Order By: Relevance
“…Our pathway analyses of the more methylated DMRs, yielded two pathways with statistical over-representation, WNT and Cadherin signaling. Both of these pathways are necessary for placental development and maturation [86][87][88][89] and a prior methylation study in PE also identified differential methylation (increased methylation) in WNT and cadherin signaling 90 , which is in agreement with our findings. Given that over 50% of PE cases have hypermaturity along with the pathological hallmarks of PE, this may indicate a role for these pathways in placental maturation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our pathway analyses of the more methylated DMRs, yielded two pathways with statistical over-representation, WNT and Cadherin signaling. Both of these pathways are necessary for placental development and maturation [86][87][88][89] and a prior methylation study in PE also identified differential methylation (increased methylation) in WNT and cadherin signaling 90 , which is in agreement with our findings. Given that over 50% of PE cases have hypermaturity along with the pathological hallmarks of PE, this may indicate a role for these pathways in placental maturation.…”
Section: Discussionsupporting
confidence: 93%
“…Our pathway analyses of the more methylated DMRs, yielded two pathways with statistical over-representation, WNT and Cadherin signaling. Both pathways are necessary for placental development and maturation [81][82][83][84] and a prior methylation study in PE also identified differential methylation (increased methylation) in WNT and cadherin signaling [85],…”
Section: Discussionmentioning
confidence: 84%
“…Subsequent KEGG pathway analysis identified genes involved in the cell adhesion molecules (CAMs) pathway to be enriched in male placentae. The physiological relevance of this finding was not discussed; however, work by others has identified an important role for CAMs in mediating appropriate placentation [34]. Therefore, the observed enrichment of the CAMs pathway in the late gestation male placentae may be an attempted male-specific compensatory adaptation to ensure continued placental invasiveness, perhaps to mitigate adverse events in late gestation brought on by suboptimal placentation.…”
Section: From Blastocyst To Neonate: Ontogeny Of Sex-specific Intrauterine Growthmentioning
confidence: 91%
“….2) using the ligands vitexin and tamoxifen. (Adu-Gyamfi et al, 2021;Zaidel-Bar, 2013). Institute of Science, BHU Varanasi, India The results depicted in Table 1 details the properties of the selected ligands vitexin and tamoxifen which clearly indicates that the vitexin has more surface area than tamoxifen which reflects in total number of atoms and their molecular weight.…”
Section: A Structure Of E-cadherinmentioning
confidence: 98%